Sliding mode control of electro-hydraulic servo system based on double observers - X. Su; X. Zheng (Mechanical Sciences, 2024)
In this paper, in order to solve the real-time state value acquisition and external-disturbance problems faced during the working process of an electro-hydraulic servo system, a sliding mode controller based on dual observers is designed, which enables the system to effectively acquire the state value and realize better control accuracy. The method uses a high-gain observer to obtain the system state in real time and then adds a perturbation observer to provide more accurate state and perturbation observations for the sliding mode controller. The dual observer observes the obtained states and external perturbations and feeds these back to the sliding mode controller to control the system accurately. Finally, the observation performance of the observers is verified by comparative simulation, and the proposed control method can improve the control accuracy.